The Ethics of Brazilian Abortion Law in the Age of Zika - Alix Masters (Voices in Bioethics, 2017)
As a woman who believes whole-heartedly in the human right to safe and legal access to abortion regardless of circumstance, it is rare I find myself balking at a movement to extend legal access to abortion.  However, in the case of Brazil’s Zika epidemic, I am struck by an ethical dilemma.  Brazil, a historically pro-life country, is currently considering reforming their anti-abortion laws exclusively in cases of fetal defects caused by Zika infection.[1] I strongly believe reproductive rights are human rights, however, if the only exceptions made in allowing safe and legal access to abortion are in cases of a disabled fetus, we as ethicists must pause. The fact that in Brazil, a country with a strong moral and legal belief in fetal personhood, lawmakers are willing to abandon this belief solely in cases of the physically and intellectually disabled presents dangerous infringements on disabled individuals’ rights.  Furthermore, advocating for legal abortion solely in the case of fetal disability is ethically wrong and has historically eugenic undertones. As a pro-choice individual, it is essential to consider the ethical concerns that exist even in movements advocating for anti-abortion law reform.